Unfree shipping: the racialisation of logistics labour. (1st April 2019) - Alimahomed-Wilson, Jake
Abstract : The logistics revolution has transformed the ways that goods are produced and transported around the world, producing numerous deleterious outcomes for workers, including the deterioration of wages and labour standards, attacks on unions, and the increase of precarious contingent labour conditions. A related, yet underexplored, process related to the logistics revolution has been the role of racialisation in further amplifying the deterioration of working conditions across the global supply chain. In this context, this article explores how the racialisation of labour impacts logistics workers in the greater Los Angeles metropolitan region. Drawing on case studies of low-wage, non-union Latinx workers in the warehouse and port trucking industries of Southern California, I argue that racialisation has accelerated the negative labour impacts related to the logistics revolution across these sectors.